DIALEKTIKA RADIKALISME DAN ANTI RADIKALISME DI PESANTREN - Kusmanto, Thohir Yuli; Fauzi, Moh.; Jamil, M. Mukhsin (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
Any effort opoosing toward any form of radicalism is a part of the reactions to anti-radicalism. The spirit of anti-radicalism emerged as part of the people's resistance. Radicalism and anti-radicalism was dialectically interrelated. Although both are paradoxical, but always be united. Dialectic of radicalism and anti-radicalism interesting is once it was observed in boarding school life. The phenomena of Islamic radicalism is often associated with Islamic boarding schools in Indonesia. Some communities understood that the growing radicalism came from Islamic boarding schools. This view was based on the the many actors of violent Islamic radicalism were the alumni of boarding school. The reality may be true in certain cases, but they may not be generalized. This study explored the data on the perspective of Islamic boarding schools on the discourse and praxis of radicalism and anti radicalism and resistance patterns. The research results showed that the community of Islamic boarding schools rejected, oppossed and actively built the spirit of anti radicalism that was implemented in several patterns. The findings of these research was a synthesis of the thesis which had become the public discourse about radicalism and Islamic boarding school.***Upaya menentang segala bentuk radikalisme merupakan bagian dari reaksi anti radikalisme. Semangat anti radikalisme muncul sebagai bagian dari resistensi masyarakat. Radikalisme dan anti radikalisme saling berkaitan secara dialektis. Meskipun keduanya merupakan sesuatu yang paradoks, namun selalu menyatu. Dialektika radikalisme dan anti radikalisme menarik ketika dilihat dalam kehidupan pesantren. Fenomena radikalisme Islam seringkali dihubungkan dengan masyarakat pesantren di Indonesia. Beberapa kelompok masyarakat memahami radikalisme tumbuh dari pesantren. Pandangan tersebut didasari oleh banyaknya pelaku radikalisme Islam dalam bentuk kekerasan alumni pesantren. Realitas tersebut bisa jadi benar dalam kasus tertentu, tetapi tidak bisa digeneralisasi. Penelitian ini berupaya menggali data pandangan pesantren tentang wacana dan praksis radikalisme dan anti radikalisme serta pola resistensinya. Hasil penelitian menunjukkan bahwa masyarakat pesantren menolak, menentang dan aktif membangun spirit anti radikalisme yang diwujudkan dalam beberapa pola. Temuan penelitian tersebut merupakan sintesis dari tesis yang selama ini menjadi wacana masyarakat tentang radikalisme dan pesantren.